The Origin and Mixed-Source Proportion of Natural Gas in the Dixin Area of the Junggar Basin: Geochemical Insights from Molecular and Isotopic Composition - Sizhe Deng; Dujie Hou; Wenli Ma (Applied Sciences, 2025)
The Dixi area of the Junggar Basin has favorable petroleum geological conditions, with the Cretaceous system representing one of the principal hydrocarbon-bearing strata. However, the genetic origin and mixing characteristics of natural gas across different tectonic zones remain insufficiently understood. In this study, a total of 65 natural gas samples were analyzed using molecular composition and stable carbon isotopic data to determine gas origins and quantify the contributions of different source rocks. A novel multivariate mathematical analysis method was developed and applied to convert compositional and isotopic data into quantitative parameters, enabling the accurate estimation of end-member mixing ratios in natural gas. This methodological innovation addresses the challenge of interpreting multi-source gas systems under complex geological conditions. The results show that the Cretaceous natural gas in the Dixi area is derived from three main sources, comprising both oil-type gas from Permian lacustrine source rocks and coal-type gas from Carboniferous coal-measure source rocks. The calculated mixing proportions exhibit significant spatial variation: in the northern Dixi area, coal-type gas dominates (67.8–84.3%), while the southern zone presents a broader mixture (25.6–68.4% coal-type gas). In the Dongdaohaizi Depression, oil-type gas is predominant, accounting for 89.4–97.7%. This study not only clarifies the genetic classification and mixing dynamics of natural gas in the Dixi area but also provides a quantitative framework for evaluating accumulation processes and source contributions in multi-source gas reservoirs. The proposed method offers valuable guidance for assessing resources and optimizing exploration strategies in the Junggar Basin and other similar basins.